A Cross-National Comparison on Subjective Well-Being of Kindergarten Teachers: Hong Kong and Italy - Benevene, Paula; Wong, Yau Ho Paul; Fiorilli, Caterina; De Stasio, Simona (Frontiers in Psychology, 2018)
Background: Teachers’ subjective well-being (SWB) has received much attention, in the light of the major increase in sick leave as well as job quitting among teachers across different cultures and countries. Studies on SWB of kindergarten teachers are still scarce, since most of the academic literature is focused on teachers of primary and secondary schools. Aims: The purpose of this study was to analyse and compare kindergarten teachers’ SWB in Hong Kong and Italy. Methods: 367 Hong Kong and 243 Italian kindergarten teachers completed a self-report questionnaire containing: the Job Satisfaction Survey (JSS), the Rosenberg Self-Esteem Scale (RSES), and the General Health Questionnaires-12 (GHQ-12). The questionnaire collected also socio-demographics data. Results: Hierarchical regression analysis showed that country belonging plays the strongest predictive role on self-esteem and mental health. Moreover, the independent t-test showed higher levels of job satisfaction among Italian teachers, while Hong Kong teachers were more satisfied in pay and promotion, but less in supervision, operating condition, co-worker relationship, nature of work, and communication. Conclusion: Results are interpreted in the light of the differences between the two contexts considered, in terms of cultural values and educational systems.